Citric acid induced phytoextraction of heavy metals from uranium contaminated soils - Scholtz, Ockert Fourie (University of the Free State, 2006)
Induced phytoextraction is an emerging soil remediation technology that makes use of soil amendments and high biomass crop species to accumulate and remove heavy metals from soils. The failure to rehabilitate an uranium trial mine on Rietkuil 307 in the Karoo Uranium Province of South Africa, has led to above normal concentrations of uranium (U), molybdenum (Mo) and arsenic (As) in topsoil in the vicinity of U ore stockpiles. A greenhouse evaluation was executed to assess the potential of citric acid to induce metal uptake in the shoots of Indian mustard [Brassica juncea (L.) Czern, cultivars: 211000 and 426308] and sunflower (Helianthus annuus L.) to decontaminate the low-level U (28 mg U kg-1 soil), Mo (4.1 mg Mo kg-1 soil) and As (8.9 mg As kg-1 soil) contaminated soil to background concentrations. A further greenhouse study was performed in a soil with high levels of metal concentrations; U (165 mg U kg-1 soil), Mo (125 mg Mo kg-1 soil) and As (49 mg As kg-1 soil), to assess the feasibility of phytoextraction on a high-level metal contaminated soil. Citric acid proved to be effective in enhancing shoot-U, -Mo and -As concentrations and the highest concentrations were observed in B. juncea 211000 (1788 mg U kg-1; 467 mg Mo kg-1; and 24 mg As kg-1) grown in the lowlevel contaminated soil. With a biomass yield of 5.51 tonnes per year for B. juncea 211000, it would take 9 to 14 years to decontaminate Mo and U on Rietkuil 307 soil to background concentrations. As a result of the low As solubility in soil and subsequent low shoot concentrations of the plant species, it is suggested that other measures for As remediation be investigated. Furthermore, plants grown in the high-level contaminated soil achieved considerably lower biomass yields and shoot-metal concentrations than in the low-level soil due to metal toxicity. Phytoextraction will, therefore, not be a feasible remediation technology on high-level U, Mo and As contaminated soils. These results suggest that citric acid induced phytoextraction may provide an environmentally friendly alternative for the decontamination of low-level U and Mo contaminated soils.

Geïndusseerde fito-ekstraksie is ‘n belowende tegnologie wat gebruik maak van grond byvoegmiddels en hoë-biomassa gewasse wat swaarmetale akkumuleer en dit sodoende uit gekontamineerde grond verwyder. Die gebrek aan rehabilitasie van ‘n uraan proefmyn op Rietkuil 307 in die Karoo Uraan Provinsie, Suid-Afrika, het tot gevolg gehad dat bogrond in die omtrek van U erts-hope, bo normale konsentrasies van uraan (U), molibdeen (Mo) en arseen (As) bevat. ’n Glashuisstudie is uitgevoer om die vermoë van sitroensuur as keleringsagent te bepaal om swaarmetaalopname in Indiese mosterd (Brassica juncea, kultivars: 211000 en 426308) en sonneblom (Helianthus annuus) te verhoog om die vlakke van U (28 mg kg-1), Mo (4.1 mg kg-1) en As (8.9 mg kg-1) in die grond na agtergrond konsentrasies te verlaag. ’n Verdere glashuisstudie is uitgevoer in grond wat hoë U (165 mg kg-1), Mo (125 mg kg-1) en As (49 mg kg-1) vlakke bevat, om die uitvoerbaarheid van fitoekstraksie in swaar gekontamineerde gronde te bepaal. Sitroensuur was doeltreffend om die metaalkonsentrasies in bogrondse plantdele te verhoog. Die hoogste konsentrasies is in B. juncea 211000 (1788 mg U kg-1 grond; 467 mg Mo kg-1 grond; and 24 mg As kg-1 grond), wat in die grond met lae metaalvlakke gegroei is, gevind. Met ’n beraamde biomassa van 5.51 ton per jaar vir B. juncea 211000, sal dit 9 tot 14 jaar vir die plant neem om die Mo en U in die bogrond van Rietkuil 307 te verminder na agtergrondvlakke. As gevolg van die lae oplosbaarheid van As in die grond en die gevolglike lae konsentrasies in die bogrondse plantdele, word dit aanbeveel dat ander remediërings metodes vir As dekontaminasie in die grond ondersoek word. Plante wat in die hoë-vlak gekontamineerde grond gegroei is, het aansienlik minder biomassa behaal in vergelyking met die plante in die lae-vlak gekontamineerde grond. As gevolg hiervan word fito-ekstraksie nie aanbeveel as ’n remediëringstegnologie vir hoë vlak U, Mo en As gekontamineerde grond nie. Die resultate verkry in hierdie studie stel voor dat sitroensuur geïndusseerde fito-ekstraksie, ’n omgewingsvriendelike alternatief vir die dekontaminasie van lae U- en Mo- vlakke in die grond kan inhou.
Dissertation (M.Sc. (Plant Sciences))--University of the Free State, 2006
Keywords: Molybdenum; Phytoextraction; Arsenic; Sunflower; Indian mustard; Citric acid; Low-level- and high-level contaminated soil; Uranium; Remediation; Karoo Uranium Province; Soil remediation; Phytoremediation; Plants -- Effect of heavy metals on; Soils -- Uranium content